2008
DOI: 10.1007/s00221-008-1569-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and cerebellar activation induced by reflexive and voluntary saccades

Abstract: ReXexive saccades are driven by visual stimulation whereas voluntary saccades require volitional control. Behavioral and lesional studies suggest that there are two separate mechanisms involved in the generation of these two types of saccades. This study investigated diVerences in cerebral and cerebellar activation between reXexive and self-paced voluntary saccadic eye movements using functional magnetic resonance imaging. In two experiments (whole brain and cerebellum) using the same paradigm, diVerences in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 74 publications
0
25
1
Order By: Relevance
“…As for fMRI studies of visual saccades in autism, we found no overlap between the areas showing between-group differences during visual saccades (frontal eye fields, dorsolateral prefrontal cortex, anterior/posterior cingulate cortex, posterior parietal cortex, precuneus, area V5, thalamus and cerebellum) and the occipital and prefrontal activity differences seen in relation to the RSPM task (Takarae, et al 2007; Thakkar, et al 2008). Moreover, none of the peaks of saccadic activity reported in the most recent studies employing non-autistic samples (frontal eye fields, supplementary eye fields, supplementary motor area, superior and middle temporal gyrus, intraparietal sulcus, basal ganglia and cerebellum) overlapped with the regions of between-group differences identified in our RSPM task (Anderson, et al 2008; Hufner, et al 2008; Schraa-Tam, et al 2009). …”
Section: Discussioncontrasting
confidence: 55%
“…As for fMRI studies of visual saccades in autism, we found no overlap between the areas showing between-group differences during visual saccades (frontal eye fields, dorsolateral prefrontal cortex, anterior/posterior cingulate cortex, posterior parietal cortex, precuneus, area V5, thalamus and cerebellum) and the occipital and prefrontal activity differences seen in relation to the RSPM task (Takarae, et al 2007; Thakkar, et al 2008). Moreover, none of the peaks of saccadic activity reported in the most recent studies employing non-autistic samples (frontal eye fields, supplementary eye fields, supplementary motor area, superior and middle temporal gyrus, intraparietal sulcus, basal ganglia and cerebellum) overlapped with the regions of between-group differences identified in our RSPM task (Anderson, et al 2008; Hufner, et al 2008; Schraa-Tam, et al 2009). …”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, the only difference between our two conditions was in the nature of the cue (exogenous vs. endogenous). Studies applying similar paradigms as the present study so far have reported inconsistent results, indicating a subtle effect on BOLD amplitude that can only be detected under certain conditions (Mort et al, 2003; Reuter et al, 2010; Schraa-Tam et al, 2009). However, in the present study the voxel pattern of activity within the sPCS could predict the direction of the forthcoming saccade only when the cue was endogenous or when volitional processes are taxed; the pattern of sPCS activity during the exogenous saccade cue could not predict saccade direction.…”
Section: Discussionmentioning
confidence: 41%
“…Using functional magnetic resonance imaging (fMRI) Mort et al (2003) compared simple internally-guided saccades and visually-guided saccades and found relatively increased activation for internally-guided saccades in the intraparietal sulcus (IPS) and in the putative human homologue of the monkey frontal eye field (FEF), which is thought to reside in the superior precentral sulcus (sPCS) at its junction with the superior frontal sulcus (Mort et al, 2003). However, other studies found the reversed pattern with higher activation in the sPCS and IPS for visually-guided saccades compared to internally-guided saccades (Schraa-Tam et al, 2009) or no difference in brain activation between the tasks (Reuter et al, 2010). …”
Section: Introductionmentioning
confidence: 85%
“…However, Schraa-Tam et al did not find a significant difference in fMRI activation of the various cerebellar regions (lobules VI and VII and HVI) during the two types of saccadic adaptation [170]. These data suggest that the amplitudes for the two types of saccades are controlled by different sets of neurons within the same cerebellar regions and/or by different networks of other brain regions such as the cerebral cortex.…”
Section: Areas Associated With Saccadic Eye Movementsmentioning
confidence: 97%